2020
DOI: 10.1038/s41438-020-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

CPPU may induce gibberellin-independent parthenocarpy associated with PbRR9 in ‘Dangshansu’ pear

Abstract: Parthenocarpy is a valuable trait in self-incompatible plants, such as pear. N-(2-chloro-4-pyridyl)-N'-phenylurea (CPPU), a synthetic cytokinin analog, can induce parthenocarpy in pear (Pyrus spp.), but the mechanism of induction is unclear. To investigate the role of gibberellin in CPPU-induced parthenocarpy in pear, CPPU supplemented with paclobutrazol (PAC) was sprayed onto 'Dangshansu' pear. We found that the fruit set rate of pear treated with CPPU supplemented with PAC was identical to that in a CPPU-alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 65 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Seedlessness, a very desirable trait that improves ease of consumption, has been bred into many fruit species, including grape 1 , litchi 2 , citrus 3 , and watermelon 4 . Previous studies have reported that phytohormones (e.g., gibberellins [GAs], auxin, and cytokinins), fertilization failure, female and male sterility, embryo abortion, and various other factors can induce the formation of seedlessness [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Seedlessness, a very desirable trait that improves ease of consumption, has been bred into many fruit species, including grape 1 , litchi 2 , citrus 3 , and watermelon 4 . Previous studies have reported that phytohormones (e.g., gibberellins [GAs], auxin, and cytokinins), fertilization failure, female and male sterility, embryo abortion, and various other factors can induce the formation of seedlessness [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…After centrifugation at 12,000 rpm for 20 min at 4 °C, the supernatant was transferred and then dried under a nitrogen gas. The dried residues were diluted in 200 μL of 50% methanol for HPLC analysis according to a previously described method …”
Section: Methodsmentioning
confidence: 99%
“…The dried residues were diluted in 200 μL of 50% methanol for HPLC analysis according to a previously described method. 39 The soluble sugar components were measured according to previous research with a minor revision. 40 In brief, approximately, 300 mg leaves were ground with liquid nitrogen and soaked with 5 mL of 80% ethanol twice at 85 °C for 30 min each time.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…CKs increase auxin concentrations, leading to parthenocarpic fruit in Pyrus spp. (pear) ( Cong et al., 2020 ), while ETH decreases bioactive GA concentrations, inhibiting parthenocarpic fruit formation in tomato ( Fos et al., 2000 ; Pascual et al., 2009 ; Shinozaki et al., 2015 ). However, a clear and systematic framework underlying the effects of various hormones on parthenocarpic fruit growth is still lacking.…”
Section: Reproductive Growthmentioning
confidence: 99%